FIQH SIYASAH PARADIGM IN THE INDICATORS OF MODERATE RELIGIOUS EDUCATION IN INDONESIA - Islamy, Athoillah; Zulihi, Zulihi; Yazid, M. Aba; Ubaidillah, Ubaidillah (Hikmah: Journal of Islamic Studies, 2025)
AbstractThe mainstreaming of moderate religious indicators in Indonesia in the realm of practice is not always responded positively by all communities. Regardless of the pros and cons, it is important to realize that the mainstreaming is a government policy to build harmony between religious, cultural and state life in Indonesia. The purpose of this qualitative study in the form of a literature review is to identify the fiqh siyasah syar'iyah paradigm on the orientation of moderate religious education contained in the indicators of religious moderation in Indonesia. This study uses a content analysis approach.  Explanations related to four indicators of moderate religiosity formulated by the Ministry of Religious Affairs of the Republic of Indonesia became the main data of the study obtained through documentation techniques. This study concludes that there are fiqh siyasah syar'iyah values in the orientation of religious moderation indicators in Indonesia that contain the dissemination of moderate religious education values, including the value of shura on indicators that require strengthening the values of pluralist and humanist religious education. Then, the value of wasathiyah on indicators that require strengthening the values of nationalist and accommodating religious education on cultural wisdom. This study shows that the indicators of moderate religiosity in Indonesia contain various legal ethical values and Islamic social education as a basis for political policy in building harmonious relations of religious, state and cultural life.AbstrakPengarustamaan indikator keberagamaan moderat di Indonesia pada ranah praksisya tidak senantiasa direspons positif oleh semua masyarakat. Terlepas dari pro-kontra yang ada, penting untuk disadari pengarustamaan tersebut menjadi kebijakan pemerintah untuk membangun harmoni antara kehidupan beragama, berbudaya dan bernegara di Indonesia. Tujuan studi kualitatif dalam bentuk kajian pustaka ini untuk mengidentifikasi paradigma fikih siyasah syar’iyah pada orientasi pendidikan keberagamaan moderat yang termuat dalam indikator moderasi beragama di Indonesia. Studi ini menggunakan pendekatan analisis isi. Penjelasan terkait empat indikator keberagamaan moderat yang dirumuskan oleh kementrian Agama Republik Indonesia menjadi data pokok studi yang diperoleh melalui teknik dokumentasi. Studi ini menyimpulkan adanya nilai-nilai fikih siyasah syar’iyah pada orientasi indikator moderasi beragama di Indonesia yang memuat diseminasi nilai-nilai pendidikan keberagamaan moderat, antara lain nilai syura pada indikator yang menghendaki penguatan nilai-nilai pendidikan keberagamaan pluralis dan humanis. Kemudian, nilai wasathiyah pada indikator yang menghendaki penguatan nilai-nilai pendidikan keberagamaan nasionalis dan akomodatif pada kearifan budaya. Studi ini menunjukan indikator keberagamaan moderat di Indonesia memuat berbagai nilai legal etik dan pendidikan sosial keberagamaan Islam sebagai basis kebijakan politik dalam membangun relasi harmoni kehidupan beragama, bernagara, dan berbudaya.